Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper on Bangladesh underlies the export performance of readymade garment industry and inflation dynamics. Bangladesh has demonstrated that it is highly competitive in the world's major garment markets. Inflation inertia, monetary factors, and exchange rate fluctuations are the main determinants of inflation in Bangladesh. Despite adoption of numerous tax policy measures during the past few years, policies implemented by the Bangladesh authorities have not been fully successful in lifting the revenue ratio to a level warranted by developmental objectives.